The Importance of Management in Journalistic Institutions - Al-Shareef, Sarab; Irani, Maytham; Al-hojjaj, Yasser Abdulzahra; Anvari, Mohammad Reza (ALBAHITH ALALAMI, 2024)
The administrative body is considered the backbone of all journalistic institutions, serving as the primary guarantee for their success and the continuity of their administrative, journalistic, and technical operations. This ensures the sustainability of their journalistic activities and their ability to attract readers. This study focuses on examining the role of management in the success of operations within journalistic institutions by analyzing the significance of newspaper management, as well as the methods, techniques, and mechanisms employed in managing journalistic, administrative, and technical work. Additionally, it explores the adopted management theories, the advancements in management science, and the extent to which journalistic institution administrations keep pace with these developments and apply them in the field of journalism.The concept of managing media institutions is a multidisciplinary research field that examines how media institutions utilize resources to meet the needs and desires of society. This concept emphasizes the effective management of media outlets.The study reached several conclusions, most notably: management serves as the cornerstone upon which journalistic institutions rely. Administrative personnel must stay abreast of technological advancements and leverage these technologies in various forms for administrative tasks, as they provide speed, precision, and efficiency in completing communication processes. Moreover, the study recommends that journalistic institutions develop improvement plans that include programs to enhance employees' skills in alignment with ongoing professional developments in journalism.